Gudeg Manggar as an Attraction of the Traditional Gastronomic Cultural Heritage - Sulistiono, Sulistiono; Wiharjo, Rahmat Yumirwan; Sulami, Evi (Journal of Tourism Education, 2022)
Currently, the Indonesian government, especially in the field of tourism, has a target to developed gastronomic tourism. Traditional food has become an important element for developing this industry.  Existence the tourist to visit tourist destinations, emerged the trend to look for authentic experiences.  Story telling cannot be separated from traditional food as then becomes the main attraction. Gastronomy industri development was comprehensive with many aspects of value-added tourism and also the gastronomic packaging can preserve the cultural heritage from ancestors then developed from generation to generation. The city of Yogyakarta has various interesting cultural heritage tourism potentials. One of the interesting concerns is the existence of Gudeg Manggar the traditional food as a cultural heritage that can become a gastronomic tourist attraction. The researcher using descriptive qualitative research method. The data obtained that this food has nine gastronomic tourism components. Then the second step after making deep interviewed and quesioner using the creativepreneurship Nona Helix model there is a finding that Gudeg Manggar can bedeveloped as Tourist attraction in Yogyakarta City.